Nano-scale activated carbon for purifying VOCs and preparation method thereof
By treating centite and activated carbon in the appropriate calcination temperature in nano-scale activated carbon, and using chitosan and salicyaldehyde for hydrophobic modification, the saturation problem after VOCs adsorption and the water increase caused by photocatalysts are solved, and the efficient VOCs degradation effect of activated carbon under visible light is achieved.
Patent Information
- Application Number
- CN202411416023.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-11
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2044-10-11
AI Technical Summary
The existing nano-scale activated carbon is prone to saturation after adsorption of VOCs and loses the adsorption effect. At the same time, the addition of photocatalysts will lead to an increase in moisture and an increase in mass transfer resistance, affecting the adsorption efficiency.
The structure of cumulite in the composite support is kept intact by a suitable calcination temperature and is combined with activated carbon to enhance the strength and specific surface area of activated carbon. Hydrophobic modification is carried out using chitosan and salicyaldehyde to promote the combination of titanium dioxide and activated carbon, and impart the VOCs degradation ability of activated carbon under visible light irradiation.
It significantly improves the adsorption efficiency and mechanical strength of activated carbon, enhances its VOCs degradation ability under visible light, and avoids the negative impact of increased moisture on adsorption efficiency.
Smart Images

Figure BDA0005079465230000081 
Figure BDA0005079465230000091
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of activated carbon and relates to a nano-scale activated carbon for purifying VOCs and a preparation method thereof. Background Art
[0002] In the field of environmental protection, nano-activated carbon has become a star material in gas phase adsorption and desorption treatment due to its excellent adsorption performance, amazing adsorption rate and outstanding plasticity. This high-tech material can not only efficiently remove harmful gases in the air, such as formaldehyde, volatile organic compounds (VOCs), etc., but also has a huge surface area due to its tiny particle size. This significant increase in surface area has made a qualitative leap in the adsorption capacity of activated carbon.
[0003] Compared with traditional activated carbon, nano-activated carbon can adsorb harmful substances in the air more quickly and thoroughly, providing a strong guarantee for improving indoor air quality and protecting human health. Although it can effectively adsorb harmful gases such as VOCs, it cannot degrade these substances. This means that after a period of adsorption, activated carbon can easily reach a saturated state and lose its original adsorption effect. In order to overcome this technical bottleneck, researchers have tried to add photocatalysts to activated carbon to achieve the degradation function of activated carbon. Although the addition of photocatalysts gives activated carbon the ability to degrade VOCs, it also brings new technical challenges. First, the moisture generated during the degradation process will interact with the hygroscopicity of activated carbon, further increasing the mass transfer resistance. This not only affects the adsorption efficiency of activated carbon, but may also have a negative impact on the catalytic effect of the photocatalyst. Secondly, since the combination of photocatalyst and activated carbon is not strong, it is easy to fall off and separate during the adsorption process. This not only reduces the adsorption and degradation efficiency of activated carbon, but also may damage the equipment and increase maintenance costs. Summary of the invention
[0004] The purpose of the present invention is to provide a nano-scale activated carbon for purifying VOCs and a preparation method thereof. The present invention maintains the structure of rectorite in a composite carrier intact by a suitable calcination temperature, and then improves the strength and specific surface area of the activated carbon by composite utilization of rectorite and activated carbon. The composite carrier is hydrophobically modified by chitosan and salicylaldehyde, which enhances the hydrophobicity and promotes the combination of titanium dioxide and activated carbon, thereby giving the activated carbon the ability to degrade VOCs under visible light irradiation.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] A method for preparing nano-scale activated carbon for purifying VOCs comprises the following steps:
[0007] 1) After cleaning the rice husk to remove dust, the rice husk is placed in a blast drying oven for drying, crushing, and sieving to obtain rice husk particles;
[0008] 2) mixing the rectorite, rice husk particles and deionized water, performing ultrasonic treatment, mechanically stirring, drying in a forced air drying oven, calcining in a muffle furnace, cooling to room temperature, washing, secondary drying and grinding to obtain a composite carrier;
[0009] 3) the composite carrier and the chitosan solution are stirred and mixed, and then ultrasonically treated, salicylaldehyde solution is added, heated and mixed, solids are filtered out, washed with alcohol, freeze-dried, titanate solution is added, stirred and mixed, and the solvent is removed by rotary evaporation to obtain a preform;
[0010] 4) Spray deionized water on the surface of the preform and vacuum dry it to obtain the preform.
[0011] As a preferred technical solution of the present invention, in step 1), the drying in the air drying oven is performed at a temperature of 60° C. to a constant weight; and the screening is performed through a 100-mesh sieve.
[0012] As a preferred technical solution of the present invention, in step 2), the mass ratio of the rectorite, rice husk particles and deionized water is 1.0-1.2:2.2-2.4:140-150.
[0013] As a preferred technical solution of the present invention, in step 2), the ultrasonic treatment is performed at a frequency of 300-400W and a temperature of 30-36°C for 30-40 minutes; the mechanical stirring is performed at a speed of 500-600r / min for 2-3 hours; and the drying is performed at a temperature of 180°C to constant weight.
[0014] As a preferred technical solution of the present invention, in step 2), the calcination is calcined at 580-600°C for 2.8-3.2h; the cleaning is performed by alternating deionized water and ethanol for three times; and the secondary drying is performed at 60-70°C to constant weight.
[0015] As a preferred technical solution of the present invention, in step 3), the mass ratio of the composite carrier, chitosan solution, salicylaldehyde solution and titanate solution is 16-20:100-120:20-30:12-14.
[0016] As a preferred technical solution of the present invention, in step 3), the concentration of the chitosan solution is 0.09wt%; the salicylaldehyde solution is prepared by mixing salicylaldehyde and anhydrous ethanol in a mass ratio of 0.2-0.3:12; and the titanate solution is prepared by mixing tetrabutyl titanate and anhydrous ethanol in a mass ratio of 3.0-3.4:15.
[0017] As a preferred technical solution of the present invention, in step 3), the ultrasonic treatment is performed at a frequency of 300-400W for 10-15min; the heating and mixing is performed at a temperature of 30-36°C for 6-8h; the alcohol washing is performed three times with a 50% mass fraction ethanol aqueous solution; and the stirring and mixing time is 40-60min.
[0018] As a preferred technical solution of the present invention, in step 4), the mass ratio of the preform to deionized water is 1:1.0-1.2; and the vacuum drying is performed at a temperature of 70-80° C. to a constant weight.
[0019] The invention discloses a nano-scale activated carbon for purifying VOCs prepared by the above-mentioned preparation method.
[0020] Beneficial effects of the present invention:
[0021] The present invention maintains the structure of rectorite in the composite carrier intact by using a suitable calcination temperature, and then improves the strength and specific surface area of the activated carbon by using the composite of rectorite and activated carbon. The composite carrier is hydrophobically modified by using chitosan and salicylaldehyde to enhance the hydrophobicity and promote the combination of titanium dioxide and activated carbon, thereby giving the activated carbon the ability to degrade VOCs under visible light irradiation. DETAILED DESCRIPTION
[0022] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.
[0023] Example 1
[0024] A method for preparing nano-scale activated carbon for purifying VOCs comprises the following steps:
[0025] 1) After cleaning the rice husk to remove dust, place it in a forced air drying oven, dry it at 60° C. to constant weight, grind it, and pass it through a 100-mesh sieve to obtain rice husk particles;
[0026] 2) After mixing the rectorite, rice husk particles and deionized water, ultrasonically treat them at a frequency of 300 W and a temperature of 30° C. for 30 min, stir them at a speed of 500 r / min for 2 h, place them in a blast drying oven, dry them at a temperature of 180° C. to constant weight, place them in a muffle furnace, calcine them at a temperature of 580° C. for 2.8 h, cool them to room temperature, wash them alternately with deionized water and ethanol three times, dry them at a temperature of 60° C. to constant weight, grind them and pass them through a 100-mesh sieve to obtain a composite carrier; wherein the mass ratio of the rectorite, rice husk particles and deionized water is 1.0:2.2:140;
[0027] 3) After the composite carrier and chitosan solution are stirred and mixed for 30 minutes, ultrasonically treated at a frequency of 300W for 10 minutes, salicylaldehyde solution is added and heated at 30°C for 6 hours, solids are filtered out, washed three times with 50% mass fraction ethanol aqueous solution and freeze-dried, titanate solution is added and stirred for 40 minutes, and the solvent is removed by rotary evaporation to obtain a preform; wherein the mass ratio of the composite carrier, chitosan solution, salicylaldehyde solution and titanate solution is 16:100:20:12; the concentration of the chitosan solution is 0.09wt%; the salicylaldehyde solution is prepared by mixing salicylaldehyde and anhydrous ethanol at a mass ratio of 0.2:12; the titanate solution is prepared by mixing tetrabutyl titanate and anhydrous ethanol at a mass ratio of 3.0:15;
[0028] 4) spraying deionized water onto the surface of the preform, and vacuum drying at 70° C. to constant weight to obtain nano-scale activated carbon; wherein the mass ratio of the preform to the deionized water is 1:1.0.
[0029] Example 2
[0030] A method for preparing nano-scale activated carbon for purifying VOCs comprises the following steps:
[0031] 1) After cleaning the rice husk to remove dust, place it in a forced air drying oven, dry it at 60° C. to constant weight, grind it, and pass it through a 100-mesh sieve to obtain rice husk particles;
[0032] 2) After mixing the rectorite, rice husk particles and deionized water, ultrasonically treat at 320W frequency and 32°C for 32 minutes, stir at 520r / min for 2.5 hours, place in a blast drying oven, dry to constant weight at 180°C, place in a muffle furnace, calcine at 585°C for 3.0 hours, cool to room temperature, wash with deionized water and ethanol alternately three times, dry to constant weight at 62°C, grind and pass through a 100-mesh sieve to obtain a composite carrier; wherein the mass ratio of the rectorite, rice husk particles and deionized water is 1.1:2.3:140;
[0033] 3) After the composite carrier and chitosan solution are stirred and mixed for 30 minutes, ultrasonically treated at a frequency of 320W for 11 minutes, salicylaldehyde solution is added and heated at 32°C for 6.5 hours, solids are filtered out, washed three times with 50% mass fraction ethanol aqueous solution and freeze-dried, titanate solution is added and stirred for 45 minutes, and the solvent is removed by rotary evaporation to obtain a preform; wherein the mass ratio of the composite carrier, chitosan solution, salicylaldehyde solution and titanate solution is 17:105:22:12.5; the concentration of the chitosan solution is 0.09wt%; the salicylaldehyde solution is prepared by mixing salicylaldehyde and anhydrous ethanol in a mass ratio of 0.22:12; the titanate solution is prepared by mixing tetrabutyl titanate and anhydrous ethanol in a mass ratio of 3.1:15;
[0034] 4) spraying deionized water onto the surface of the preform, and vacuum drying at 72° C. to constant weight to obtain nano-scale activated carbon; wherein the mass ratio of the preform to the deionized water is 1:1.05.
[0035] Example 3
[0036] A method for preparing nano-scale activated carbon for purifying VOCs comprises the following steps:
[0037] 1) After cleaning the rice husk to remove dust, place it in a forced air drying oven, dry it at 60° C. to constant weight, grind it, and pass it through a 100-mesh sieve to obtain rice husk particles;
[0038] 2) After mixing the rectorite, rice husk particles and deionized water, ultrasonically treat at 350W frequency and 33°C for 35 minutes, stir at 550r / min for 2.5 hours, place in a blast drying oven, dry to constant weight at 180°C, place in a muffle furnace, calcine at 590°C for 3 hours, cool to room temperature, wash with deionized water and ethanol alternately three times, dry to constant weight at 65°C, grind and pass through a 100-mesh sieve to obtain a composite carrier; wherein the mass ratio of the rectorite, rice husk particles and deionized water is 1.1:2.3:145;
[0039] 3) After the composite carrier and chitosan solution are stirred and mixed for 30 minutes, ultrasonically treated at a frequency of 350W for 12 minutes, salicylaldehyde solution is added and heated at 33°C for 7 hours, solids are filtered out, washed three times with 50% mass fraction ethanol aqueous solution and freeze-dried, titanate solution is added and stirred for 50 minutes, and the solvent is removed by rotary evaporation to obtain a preform; wherein the mass ratio of the composite carrier, chitosan solution, salicylaldehyde solution and titanate solution is 18:110:25:13; the concentration of the chitosan solution is 0.09wt%; the salicylaldehyde solution is prepared by mixing salicylaldehyde and anhydrous ethanol in a mass ratio of 0.25:12; the titanate solution is prepared by mixing tetrabutyl titanate and anhydrous ethanol in a mass ratio of 3.2:15;
[0040] 4) spraying deionized water onto the surface of the preform, and vacuum drying at 75° C. to constant weight to obtain nano-scale activated carbon; wherein the mass ratio of the preform to the deionized water is 1:1.1.
[0041] Example 4
[0042] A method for preparing nano-scale activated carbon for purifying VOCs comprises the following steps:
[0043] 1) After cleaning the rice husk to remove dust, place it in a forced air drying oven, dry it at 60° C. to constant weight, grind it, and pass it through a 100-mesh sieve to obtain rice husk particles;
[0044] 2) After mixing the rectorite, rice husk particles and deionized water, ultrasonically treat at 370W frequency and 34°C for 38 minutes, stir at 570r / min for 2.8 hours, place in a blast drying oven, dry to constant weight at 180°C, place in a muffle furnace, calcine at 595°C for 3.0 hours, cool to room temperature, wash with deionized water and ethanol alternately three times, dry to constant weight at 68°C, grind and pass through a 100-mesh sieve to obtain a composite carrier; wherein the mass ratio of the rectorite, rice husk particles and deionized water is 1.15:2.4:148;
[0045] 3) After the composite carrier and chitosan solution are stirred and mixed for 30 minutes, ultrasonically treated at a frequency of 370W for 14 minutes, salicylaldehyde solution is added and heated at 34°C for 7.5 hours, solids are filtered out, washed three times with 50% mass fraction ethanol aqueous solution and freeze-dried, titanate solution is added and stirred for 55 minutes, and the solvent is removed by rotary evaporation to obtain a preform; wherein the mass ratio of the composite carrier, chitosan solution, salicylaldehyde solution and titanate solution is 19:115:28:13.5; the concentration of the chitosan solution is 0.09wt%; the salicylaldehyde solution is prepared by mixing salicylaldehyde and anhydrous ethanol in a mass ratio of 0.28:12; the titanate solution is prepared by mixing tetrabutyl titanate and anhydrous ethanol in a mass ratio of 3.3:15;
[0046] 4) spraying deionized water onto the surface of the preform, and vacuum drying at 78° C. to constant weight to obtain nano-scale activated carbon; wherein the mass ratio of the preform to the deionized water is 1:1.15.
[0047] Example 5
[0048] A method for preparing nano-scale activated carbon for purifying VOCs comprises the following steps:
[0049] 1) After cleaning the rice husk to remove dust, place it in a forced air drying oven, dry it at 60° C. to constant weight, grind it, and pass it through a 100-mesh sieve to obtain rice husk particles;
[0050] 2) After mixing rectorite, rice husk particles and deionized water, ultrasonically treat at 400W frequency and 36°C for 40 minutes, stir at 600r / min for 3 hours, place in a blast drying oven, dry to constant weight at 180°C, place in a muffle furnace, calcine at 600°C for 3.2 hours, cool to room temperature, wash with deionized water and ethanol alternately three times, dry to constant weight at 70°C, grind and pass through a 100-mesh sieve to obtain a composite carrier; wherein the mass ratio of rectorite, rice husk particles and deionized water is 1.2:2.4:150;
[0051] 3) After the composite carrier and chitosan solution are stirred and mixed for 30 minutes, ultrasonically treated at a frequency of 400W for 15 minutes, salicylaldehyde solution is added and heated at 36°C for 8 hours, solids are filtered out, washed three times with 50% mass fraction ethanol aqueous solution and freeze-dried, titanate solution is added and stirred for 60 minutes, and the solvent is removed by rotary evaporation to obtain a preform; wherein the mass ratio of the composite carrier, chitosan solution, salicylaldehyde solution and titanate solution is 20:120:30:14; the concentration of the chitosan solution is 0.09wt%; the salicylaldehyde solution is prepared by mixing salicylaldehyde and anhydrous ethanol in a mass ratio of 0.3:12; the titanate solution is prepared by mixing tetrabutyl titanate and anhydrous ethanol in a mass ratio of 3.4:15;
[0052] 4) spraying deionized water onto the surface of the preform, and vacuum drying at 80° C. to constant weight to obtain nano-scale activated carbon; wherein the mass ratio of the preform to the deionized water is 1:1.2.
[0053] Comparative Example 1
[0054] Compared with Example 4, Comparative Example 1 is different in that no rectorite is used, and the remaining components, preparation steps and parameters are the same.
[0055] Comparative Example 2
[0056] Compared with Example 4, Comparative Example 2 is different in that chitosan is not used, and the other components, preparation steps and parameters are the same.
[0057] Comparative Example 3
[0058] Compared with Example 4, Comparative Example 3 is different in that salicylaldehyde is not used, and the remaining components, preparation steps and parameters are the same.
[0059] Comparative Example 4
[0060] Compared with Example 4, Comparative Example 4 is different in that nano-titanium dioxide is used instead of titanate, and the other components, preparation steps and parameters are the same.
[0061] Comparative Example 5
[0062] Compared with Example 4, the difference in Comparative Example 5 is that the calcination process in step 2) is calcined at 650° C. for 3.0 h, and the other components, preparation steps and parameters are the same.
[0063] The nano activated carbons obtained from Examples 1-5 and Comparative Examples 1-5 were subjected to the following tests, respectively. The test results are shown in Table 1.
[0064] Degradation test: The photocatalytic degradation test was carried out according to GB / T 23761-2009. The amount of activated carbon was 0.5g, the test gas was formaldehyde, the initial concentration was 10mg / L, and the visible light illumination time was 10h.
[0065] Table 1
[0066]
[0067]
[0068] From the test results in Table 1, it can be seen that compared with Comparative Examples 1-5, the nano-activated carbon prepared in Examples 1-5 has a more significant ability to remove formaldehyde.
[0069] Through comparative analysis, it can be known that the present invention maintains the structure of the rectorite in the composite carrier intact by using a suitable calcination temperature; when the calcination temperature is too high, the crystal face of the rectorite disappears, its structure is destroyed, the specific surface area becomes smaller, and the active sites are reduced, so the photocatalytic degradation performance of the nano activated carbon is reduced; the present invention uses the composite utilization of rectorite and activated carbon, and with the help of the negative charge characteristics of the rectorite surface, not only improves the mechanical strength and specific surface area of the activated carbon, but also significantly improves the adsorption efficiency and performance in the filtration and adsorption applications of volatile organic compounds. In addition, the present invention uses chitosan and salicylaldehyde to modify the hydrophobicity of the composite carrier, effectively removes the moisture in the pores of the composite carrier, and enhances its overall hydrophobicity. At the same time, the imine bond and oxygen-containing functional group in the chitosan / salicylic aldehyde compound promote the combination of titanium dioxide and activated carbon through hydrogen bonding and electrostatic adsorption, giving the activated carbon the ability to degrade VOCs under visible light irradiation. On the other hand, through the in-situ hydrolysis of titanate on the surface of the preform, the roughness of the surface of the nano-activated carbon is increased, making its surface superhydrophobic, thereby enhancing the photocatalytic effect of the surface and enabling it to have efficient adsorption and degradation properties for volatile formaldehyde.
[0070] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A method for preparing nano-scale activated carbon for purifying VOCs, characterized in that: The preparation method comprises the following steps: 1) After cleaning the rice husk to remove dust, place it in a blast drying oven for drying, crushing, and sieving to obtain rice husk particles; 2) mixing rectorite, rice husk particles and deionized water, performing ultrasonic treatment, mechanically stirring, drying in a forced air drying oven, calcining in a muffle furnace, cooling to room temperature, washing, secondary drying and grinding to obtain a composite carrier; 3) The composite carrier and chitosan solution are stirred and mixed, and then ultrasonically treated. The salicylaldehyde solution is added, heated and mixed, and then the solid is filtered out, washed with alcohol, and then freeze-dried. The titanate solution is added, stirred and mixed, and the solvent is removed by rotary evaporation to obtain a preform; 4) Spray deionized water on the surface of the preform and dry it in vacuum to obtain; In step 2), the mechanical stirring is stirring at a speed of 500-600 r / min for 2-3 hours; the drying is drying at a temperature of 180° C. to constant weight; the calcination is calcining at a temperature of 580-600° C. for 2.8-3.2 hours; and the secondary drying is drying at a temperature of 60-70° C. to constant weight.
2. The method for preparing nano-scale activated carbon for purifying VOCs according to claim 1, characterized in that: In step 1), the drying in the air drying oven is performed at a temperature of 60° C. to a constant weight; and the sieving is performed through a 100-mesh sieve.
3. The method for preparing nano-scale activated carbon for purifying VOCs according to claim 1, characterized in that: In step 2), the mass ratio of the rectorite, the rice husk particles and the deionized water is 1.0-1.2:2.2-2.4:140-150.
4. The method for preparing nano-scale activated carbon for purifying VOCs according to claim 1, characterized in that: In step 2), the ultrasonic treatment is performed at a frequency of 300-400 W and a temperature of 30-36° C. for 30-40 min.
5. The method for preparing nano-scale activated carbon for purifying VOCs according to claim 1, characterized in that: In step 2), the cleaning is performed by alternately using deionized water and ethanol for three times.
6. The method for preparing nano-scale activated carbon for purifying VOCs according to claim 1, characterized in that: In step 3), the mass ratio of the composite carrier, chitosan solution, salicylaldehyde solution and titanate solution is 16-20:100-120:20-30:12-14.
7. The method for preparing nano-scale activated carbon for purifying VOCs according to claim 1, characterized in that: In step 3), the concentration of the chitosan solution is 0.09wt%; the salicylaldehyde solution is prepared by mixing salicylaldehyde and anhydrous ethanol at a mass ratio of 0.2-0.3:12; and the titanate solution is prepared by mixing tetrabutyl titanate and anhydrous ethanol at a mass ratio of 3.0-3.4:
15.
8. The method for preparing nano-scale activated carbon for purifying VOCs according to claim 1, characterized in that: In step 3), the ultrasonic treatment is performed at a frequency of 300-400W for 10-15 minutes; the heating and mixing is performed at a temperature of 30-36°C for 6-8 hours; the alcohol washing is performed three times with a 50% mass fraction ethanol aqueous solution; and the stirring and mixing time is 40-60 minutes.
9. The method for preparing nano-scale activated carbon for purifying VOCs according to claim 1, characterized in that: In step 4), the mass ratio of the preform to deionized water is 1:1.0-1.2; and the vacuum drying is performed at a temperature of 70-80° C. to a constant weight.
10. A nano-scale activated carbon for purifying VOCs prepared by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Method for preparing adsorbent by coupling chitosan with bamboo charcoal by using monoaldehyde
CN101955551A
Hydrophobic activated carbon adsorbent for treating high-humidity VOCs and preparation method of hydrophobic activated carbon adsorbent
CN111330543A